Perancangan Media Promosi Whatsapp Web dan Facebook Market Place Produk Kerang pada Koperasi Ikhtiar Swadaya Mitra (ISM) Karya Sinar Bahari, Desa Tanggul Jaya, Kelurahan Banten, Kecamatan Kasemen, Kota Serang, Provinsi Banten - Umami, Riza; Safitri, Hindun; Uryanti, Yaya; Ahdani, Udin; Sudaryana, Yayan (Jurnal PKM Manajemen Bisnis, 2024)
This service is entitled Promotional Media Design on Whatsapp business and Facebook Market place at the Karya Sinar Bahari Cooperative (KSB) Tanggul Jaya Village, District. Kasemen, Serang City, Banten Province. The main objective of this community service activity is to provide education about methods and steps to open a distribution network through designing wider promotional media efficiently and effectively to achieve profitable product selling prices, choosing media that is efficient and suitable for product promotion. green mussels and determining the appropriate media placement to promote green mussel products by the Karya Sinar Bahari Cooperative (KSB) Tanggul Jaya Village, Kec. Kasemen, Serang City. The method used is a survey method and direct delivery of material as well as simulations and discussions regarding the science of marketing management in the digital era as well as creating a WhatsApp business account along with photos of the green mussel catalog products.